Does stock trading volume signal future dividends? Evidence from Iberian firms - Lobão, Júlio (2022)
In the study we test the theory that financial markets can provide relevant information about forthcoming corporate events. More specifically, we examine the ability of trading volume to predict dividend changes in a sample of 880 dividend announcements from Iberian firms for the period 2005–2018. We document evidence of a positive and significant relation between unusually high volume and subsequent dividend changes. The results based on panel data regressions with control variables for firm size, profitability measures, volatility and average turnover using both pooled OLS method and fixed effects method are robust. Our results are of special interest to those investors that exhibit a higher preference for dividends.